Parents’ perception on grade 5 students’ learning activity using WhatsApp - Dina Intan Sukmayanti (ETUDE: Journal of Educational Research, 2021)
Background: Various educational applications have been provided by the government that can be accessed and used by teachers or students as support for the online learning process. Most of the educators in elementary schools only use the WhatsApp group application. Purpose: This study aims to determine how parents respond to online learning through Whatsapp groups during the pandemic. Design and methods: This study uses a narrative analysis method with a qualitative approach. The population of this study were 20 parents of grade 5 students at SDN Tajur 01. The data were collected through indirect interviews in the form of a digital questionnaire distributed via WhatsApp. To find out the validity of the information from the questionnaire results, it was analyzed then summarized and arranged regularly. The questionnaire information is considered legal because it comes from the parents of elementary school students. Results: The results of this study reveal the responses of parents, namely: 1) The majority of parents of grade 5 students said that it was true that teachers only used the WhatsApp application as an online learning medium in elementary schools; 2) The learning process via WhatsApp group starts every morning by providing learning materials and certain assignments through audio, voice and text according to the learning schedule; 3) The rarely detailed video explanation of the lesson given by the teacher causes the child to have difficulty understanding the subject matter; 4) Through WhatsApp groups, which are felt to quickly bore children studying at home; 5) The activeness of children in online learning can be seen by always working on assignments via the WhatsApp group. This research includes only one school in Citeureup. The use of the WhatsApp application as a learning medium for teachers and students should be re-evaluated.